Mineral nutrition of rubber tree: I - Growth and recruitment of macronutrients by the Hevea brasiliensis Mull. Arg., clone Fx 3864 in a four year periods at Rio Branco, AC, Brazil - Guerrini, I.; Haag, H.P.; Weber, H.; Dechen, A.R. (Anais da Escola Superior de Agricultura Luiz de Queiroz, 1983)
Primary objective of this work was to study the growth, and concentration and accumulation of macronutrierts on the Hevea brasiliensis plants, at various ages. Leaves, stems and branches of rubber tree clone Fx 3864 from one year up to years old were collected from a plantation located at the BONAL S.A. farm at Rio Branco, Brasil the soil under the forest was classified as a heavy texture Red-Yellow Latosol. Results obtained showed that: - Highest growth increment occured from the third year on. - The leaves had the highest nutrient concentration - During the fourth year, nutrient extraction per hectare was: N - 24.54 kg, P - 1.82 kg, K - 18.29 kg, Ca - 11.07 kg, Mg - 5-29 kg, S - 1,88 kg. - Total macronutrients were absorbed in the following decreasing order: N, K, Ca, Mg, S, P.